The evaluation of exercise-induced hematuria in endurance athletes - Marshall, G.; Jarial, D.; Durbin, J (The Sport Journal, 2017)
Microscopic hematuria can be defined as the presence of greater (>) than 3 red blood cells per milliliter (mL) detected on a high-powered microscopic field, or > 50 red blood cells per mL of urine present on a urine dipstick (14). Exercise-induced hematuria in healthy young adults is not usually associated with significant morbidity or mortality (15). Moderate exercise-induced hematuria is seen habitually, both in athletes and in the general public (14). However, hematuria can be a signal of more serious diseases (15). In endurance athletes, the microscopic hematuria is often self-limiting and resolves within 48-72 hours (1). The abnormal presence of red blood cells in urine may indicate kidney inflammation, infection or trauma in the urinary tract, or neoplastic diseases in the urogenital tract (6). If hematuria doesn`t resolve within 48-72 hours, providers should consider further evaluation. Diagnostics and interventions should be adapted to the individual based on the history of present illness, age, and past medical history. Future research on this topic could be adapted to evaluating and treating microscopic hematuria in multiple sports and activities.